Prediction Of Corporate Failure : A Study Of The Malaysian Corporate Sector - Chin , Nyuk Sang (2005)
Financial ratios have been used as a tool to predict corporate events and more significantly, used to build bankrupty models to predict corporate failure. This study employs a Multivariate Discriminant Analysis (MDA) approach to develop 3 discriminant functions that can divide companies into bankruptcy-prone and healthy companies, based on 65 financial ratios.